2024
DOI: 10.1039/d3ma00797a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticles as efficient verteporfin nanocarriers for photodynamic therapy of cancer

Tomás Mendes,
Andreia Granja,
Salette Reis

Abstract: A lipid nanoformulation was developed for encapsulating the photosensitizer verteporfin. Upon irradiation with a LED at 690 nm the nanoparticles demonstrated a dose-dependent anti-cancer effect an enhanced production of reactive oxygen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…In another study, Mendes et al developed an LNP formulation of BPD and demonstrated that the LNPs improved the water solubility of BPD. They also maintained PDT efficiency in breast cancer cells, killing 70% of cells when treated with 0.5 μM BPD equivalent concentration of LNPs, followed by irradiation with 690 nm light for 5 min at an irradiance of 6.7 mW/cm 2 . These LNPs encapsulating BPD were synthesized from cetly palmate and tween 80 and exhibited a hydrodynamic size of 193 nm with a PDI of 0.16.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Mendes et al developed an LNP formulation of BPD and demonstrated that the LNPs improved the water solubility of BPD. They also maintained PDT efficiency in breast cancer cells, killing 70% of cells when treated with 0.5 μM BPD equivalent concentration of LNPs, followed by irradiation with 690 nm light for 5 min at an irradiance of 6.7 mW/cm 2 . These LNPs encapsulating BPD were synthesized from cetly palmate and tween 80 and exhibited a hydrodynamic size of 193 nm with a PDI of 0.16.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LNPs have been approved as mRNA delivery vehicles in vaccines developed for COVID-19, and a Nobel Prize was awarded in 2023 for pioneering work on LNP-based vaccines . While existing research has primarily focused on LNP applications in drug delivery and vaccine technologies, only a few studies have investigated the potential for LNPs as effective photosensitizer delivery platforms for PDT. Sohoo et al encapsulated methyl pyro­pheophorbide-a (MPPa), a hydrophobic photosensitizer, in LNPs and demonstrated an increase in water solubility of the photosensitizer and an improvement in PDT efficacy. They used a combination of different lipids (palmitic acid, steric acid, and glycerol monostearate) and surfactants (poloxamer 188, poloxamer 488, and tween 80) to synthesize and compare ten different formulations loaded with MPPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation